Wavelength calibration and spectral sensitivity correction of luminescence measurements for dosimetry applications: Method comparison tested on the IR-RF of K-feldspar. (December 2022) - Sontag-González, Mariana; Mittelstraß, Dirk; Kreutzer, Sebastian; Fuchs, Markus
Abstract: Spectroscopic investigations provide important insights into the composition of luminescence emissions relevant to trapped-charge dating of sediments. Accurate wavelength calibration and a correction for the wavelength-dependent detection efficiency of the spectrometer system are crucial to ensure the correct spectrum interpretation and allow for its comparison with those obtained from other systems. However, to achieve an accurate detection efficiency correction, it is necessary to obtain the device-specific spectral response function (SRF). Here, we compare two SRF approximation methods by using either a calibration lamp of known irradiance or calculating the product of efficiency curves provided by the manufacturers of all known optical elements. We discuss the results using radiofluorescence (RF) measurements of two K-feldspar samples as an example. Feldspar infra-red (IR) RF spectra are known to be composed of several overlapping emissions, whose variation with sample mineralogy is still poorly understood and requires more extensive investigations. We find that both methods of sensitivity correction yield broadly similar results. However, the observed differences can alter a spectrum's interpretation. For example, we observe that after peak deconvolution the maximum signal wavelength of the IR-RF peak used for dating applications differs by ∼3–13 nm between the two methods, depending on sample and diffraction grating. We recommend using calibration lamps to determine a device's SRF but highlight the need to consider issues such as higher-order signals in the choice of filters to establish the SRF's reliable wavelength range. Additionally, we find that a simple and inexpensive fluorescent white light yields an acceptable wavelength calibration comparable to that obtained from a specialized light source. Highlights: An inexpensive fluorescent white light yields an acceptable wavelength calibration. Sensitivity correction can be approximated from the efficiency of optical elements. The second-order signal of a reference calibration lamp needs to be accounted for. Different correction methods lead to different deconvoluted IR-RF peak wavelengths. Associated R code is provided.